SISTEM APLIKASI PERSEDIAAN BARANG JADI MENGGUNAKAN METODE FIFO PADA PT.PRIMA INDAH UNTUK MENGHINDARI REDUNDANSI LAPORAN PERSEDIAAN - Damayanti, Tria; Rayuni, Rayuni; Maulita, Yani; Fauzi, Achmad (Majalah Ilmiah Kaputama, 2017)
In the rapid technological developments and rapidly prosecute any businesses or other institutions to further improve any systems used in management. Expected every facet of business activity using a computerized system . Likewise with existing technology PT. Prima Indah. PT. Prima Indah in the calculation of finished goods inventory still using manual systems and cause problems in the form of ever making the report and the absence of a special database that stores data inventory . So it needs a special system that handles the calculation of finished goods inventories in order to facilitate the knowing of finished goods inventory in the warehouse . In that regard there are some things that should be discussed about how the calculation of finished goods inventory at PT. Prima Indah and how the entrance and exit of preparing reports and statements of finished goods inventory accumulation .            The final task is to try to discuss and analyze problems that occur in the calculation of the inventory of finished goods . And the result will be directed to the company as a suggestion to use a computerized system in order to save costs and time as well as the accuracy of the information produced .